(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Financial Feasibility Analysis of Arabica Coffee Farming in Belok Sidan Village, Petang Sub-district, Badung Regency. This study evaluates the financial feasibility of Arabica coffee farming in Belok Sidan Village, Petang Sub-district, Badung Regency, a region characterized by optimal agroclimatic conditions for Arabica coffee cultivation. The research focuses on assessing the profitability and resilience of the farming enterprise under varying scenarios of price and production fluctuations. A quantitative approach was employed, utilizing investment appraisal indicators including Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit-Cost Ratio (Net B/C). Primary data were collected from 40 coffee farmers through structured questionnaires and interviews, while secondary data were obtained from relevant institutions and literature sources. The results indicate that Arabica coffee farming in the study area is financially feasible, with an NPV of IDR 74,406,428, an IRR of 16.18%, and a Net B/C ratio of 1.69. These indicators reflect efficient capital allocation and the ability of the enterprise to generate substantial economic surplus. Sensitivity analysis shows that the business remains viable under a 25% decline in selling price or a 30% reduction in production volume. Simultaneous declines in both variables render the enterprise financially unfeasible, as evidenced by the downward shift of IRR and Net B/C below acceptable thresholds. These findings underscore the importance of risk-based planning and adaptive farm management in mitigating market volatility and production risks. The study provides empirical insights to inform strategic decision-making for farmers, policymakers, and stakeholders in fostering a sustainable Arabica coffee agribusiness model.